2021
DOI: 10.22159/ijap.2021v13i2.40270
|View full text |Cite
|
Sign up to set email alerts
|

Setting Time, Flowability, and Solubility of Epoxy Resin-Based Sealer Mixed With Chitosan Nanoparticles

Abstract: Objective: The purpose of this study was to investigate the effect of the incorporation of chitosan nanoparticles into epoxy resin-based sealer on its setting time, flowability and solubility.  Methods: This study was divided into three evaluations: setting time, flowability, and solubility of sealers. Each study used 20 samples, which were divided into two groups. Group 1, epoxy resin-based sealers, and group 2, epoxy resin-based sealers mixed with chitosan nanoparticles. The Gilmore needle was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It provides information about the degree of crystallinity and the crystalline composition [ 57 ]. The crystallinity of the dental materials provides stability and preservation of the structural integrity against degradation and solubility of the materials by the action of the environment [ 47 , 58 , 59 ]. While, XRF analysis is a rapid, and accurate test to detect chemical elemental compositions [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It provides information about the degree of crystallinity and the crystalline composition [ 57 ]. The crystallinity of the dental materials provides stability and preservation of the structural integrity against degradation and solubility of the materials by the action of the environment [ 47 , 58 , 59 ]. While, XRF analysis is a rapid, and accurate test to detect chemical elemental compositions [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the crystallinity of the dental materials provides thermal stability and preservation of the structural integrity against degradation and solubility of the materials by the action of the environment 34 , 35 , still, the presence of some degree of amorphous phase permits a reasonable grade of solubility and ions leaching responsible for pH changes and precipitation, which are essential for remineralization, sealing, and tissue healing 36 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the addition of chitosan nanoparticles to ERB sealer did not affect the physical properties of ERB sealer, which exhibited acceptable sealer for obturation material. [11][12][13] However, until now there is deliberation about the appropriate concentration of chitosan nanoparticles, which should be added to sealer. Thus, the purpose of this study was to evaluate the addition of nanoparticle chitosan with concentrations of 0, 10, 20, and 30% to the ERB sealer on its antibacterial and cytotoxicity effect.…”
mentioning
confidence: 99%
“…Previous studies have shown that the addition of chitosan nanoparticles to ERB sealer did not affect the physical properties of ERB sealer, which exhibited acceptable sealer for obturation material. 11 12 13 …”
mentioning
confidence: 99%